Abrasive slurry and polishing method therewith
The abrasive slurry with manganese oxide particles and additives improves dispersibility and polishing efficiency, addressing clogging and adherence issues, and extends pot life, enhancing cleaning ease and reducing environmental burden.
Patent Information
- Application Number
- JP2023571423
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-06-20
AI Technical Summary
Existing abrasive slurries containing manganese oxide particles suffer from poor dispersibility, leading to clogging of supply tubes, adherence to polished surfaces, and short pot life, which complicates cleaning and prolongs polishing times.
An abrasive slurry comprising manganese oxide abrasive grains, permanganate ions, phosphoric acids, polycarboxylic acids, polycarboxylic acid salts, naphthalenesulfonic acid formalin condensates, and water-soluble organic polymers like polyvinyl pyrrolidone and polyvinyl alcohol, enhancing dispersibility and polishing rate while extending pot life.
The slurry exhibits excellent dispersibility, high polishing rate, and prolonged pot life, facilitating easy cleaning and reducing environmental impact by minimizing wastewater, and shortening polishing time.
Smart Images

Figure 0007610041000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an abrasive slurry and a polishing method using the same. [Background technology]
[0002] Among semiconductor devices, power semiconductor elements known as power devices are being required to withstand higher voltages and currents by using silicon carbide (SiC), gallium nitride, diamond, etc. instead of the silicon that has traditionally been used as a substrate. Substrates made of these materials have a larger band gap than conventional silicon substrates, making them capable of withstanding higher voltages.
[0003] Among them, a substrate made of silicon carbide (hereinafter referred to as a SiC substrate) is excellent not only in hardness, heat resistance, and chemical stability, but also in terms of cost. On the other hand, since a SiC substrate is harder than a conventional silicon substrate, an abrasive slurry containing manganese oxide particles as abrasive grains has been developed as disclosed in Patent Document 1, for example, as an abrasive slurry used in a polishing step by a so-called CMP (Chemical Mechanical Polishing) method or the like, which is a step of mirror-finishing the surface of a SiC substrate during the manufacturing process of the SiC substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-071787 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, as disclosed in Patent Document 1, many of the abrasive slurries containing manganese oxide particles as abrasive grains have insufficient dispersibility, and since the abrasive slurry is in a viscous liquid state, there is a problem that the supply tube for supplying the abrasive slurry is easily clogged. In addition, during the polishing process, the abrasive slurry adheres to the surface of the SiC substrate to be polished and to the polishing pad and other equipment used for polishing, so that when cleaning the polishing pad and SiC substrate after the polishing process, the abrasive slurry is difficult to remove, and the cleaning process takes time. Such abrasive slurries tend to have a short pot life.
[0006] In view of the above problems, the present invention provides an abrasive slurry having excellent dispersibility, a high polishing rate, and a long pot life, and a polishing method. [Means for solving the problem]
[0007] The abrasive slurry of the present invention, which has been made to solve the above problems, is characterized by having manganese oxide abrasive grains containing manganese oxide particles, permanganate ions, phosphoric acids, and a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formalin condensates, polyvinyl alcohol, polyethylene glucose, polyvinylpyrrolidone, and copolymers thereof. The abrasive slurry of the present invention has excellent dispersibility, a high polishing rate, and a long pot life due to the inclusion of manganese oxide abrasive grains containing manganese oxide particles, permanganate ions, phosphoric acids, and a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formalin condensates, polyvinyl alcohol, polyethylene glucose, polyvinylpyrrolidone, and copolymers thereof. In addition, the abrasive slurry according to the present invention has excellent dispersibility, and therefore, the polished object, i.e., the SiC substrate or polishing pad, can be easily washed, and the amount of washing water used can be reduced, the washing time can be shortened, and the amount of wastewater to be treated can be reduced, which leads to a reduction in the environmental load. Furthermore, the abrasive slurry according to the present invention exhibits a high polishing rate, and therefore, the polishing process time can be shortened.
[0008] Examples of manganese oxide particles contained in the manganese oxide abrasive grains include manganese oxide (II) (MnO), dimanganese trioxide (III) (Mn2O3), manganese dioxide (IV) (MnO2), trimanganese tetroxide (II, III) (Mn3O4), etc. The manganese oxide abrasive grains may be a mixture of one type or two or more types of manganese oxide particles.
[0009] In addition, the manganese oxide abrasive grains may contain abrasive grains other than the above-mentioned manganese oxide grains, so long as the effect of preventing warpage and cracking due to the Twyman effect on the polished object, for example, a SiC substrate, of the abrasive slurry of the present invention is not impaired. Examples of abrasive grains other than manganese oxide grains include compounds such as oxides, hydroxides, and carbides of at least one element selected from Mg, B, Si, Ce, Al, Zr, Fe, Ti, and Cr, and other carbon materials. Specific examples include alumina, silica, cerium oxide, zirconium oxide, titanium oxide, chromium oxide, iron oxide, magnesium hydroxide, cerium hydroxide, silicon carbide, boron carbide, and diamond. These may be used alone or in combination of two or more. In addition, the manganese oxide grains may be composited with abrasive grains other than manganese oxide grains, for example, manganese oxide grains surface-coated with abrasive grains other than manganese oxide grains, or manganese oxide grains surface-coated with abrasive grains other than manganese oxide grains.
[0010] Moreover, it is preferable that the manganese oxide abrasive grains have a particle size (D50) at 50% of the cumulative volume as measured by a laser diffraction / scattering particle size distribution measurement method of 0.1 μm or more in terms of having a high polishing power, and it is preferable that the particle size is 5.0 μm or less in terms of suppressing roughness of the surface of the workpiece to be polished, such as a SiC substrate. Therefore, it is more preferable that the manganese oxide abrasive grains have a particle size (D50) at 50% of the cumulative volume as measured by a laser diffraction / scattering particle size distribution measurement method of 0.15 μm or more and 4.5 μm or less, and even more preferable that the particle size is 0.2 μm or more and 4.0 μm or less.
[0011] Here, the particle size at 50% cumulative volume (D50) of manganese oxide abrasive grains measured by a laser diffraction / scattering particle size distribution measurement method is prepared by diluting a mixture of manganese oxide abrasive grains pulverized with beads in the manufacturing method of an abrasive slurry of the present invention described below with water so that the concentration of this mixture becomes about 0.01%. Then, the measurement is carried out using a laser diffraction / scattering particle size distribution measurement device (MT3300EXII manufactured by Microtrackbell Co., Ltd.).
[0012] Furthermore, the content of manganese oxide abrasive grains contained in the abrasive slurry of the present invention is preferably 0.5% by mass or more and 20% by mass or less, more preferably 0.5% by mass or more and 10% by mass or less, based on the total amount of the abrasive slurry, from the viewpoint of sufficiently increasing the polishing rate of high-hardness materials such as silicon carbide, from the viewpoint of ensuring the suitable fluidity of abrasive grains in the abrasive slurry, and from the viewpoint of preventing aggregation.In addition, the content of manganese oxide particles contained in the manganese oxide abrasive grains is more preferably 1% by mass or more and 5% by mass or less, from the viewpoint of sufficiently increasing the polishing rate.In addition, in this specification, the content in the abrasive slurry of the present invention is the content in the abrasive slurry before polishing begins, unless otherwise specified.
[0013] Furthermore, the abrasive slurry of the present invention contains, in addition to the manganese oxide abrasive grains described above, permanganate ions (MnO4 -) The permanganate ion, when used in combination with manganese oxide abrasive grains as an oxidizing agent, can have a high polishing power for high-hardness materials such as silicon carbide. Here, the source of the permanganate ion is preferably a permanganate. Examples of the permanganate include an alkali metal salt of permanganate and an alkaline earth metal salt of permanganate. Furthermore, from the viewpoint of easy availability and improving the polishing efficiency of the abrasive slurry of the present invention, among the permanganates that are the source of the permanganate ion, an alkali metal salt of permanganate is preferred, and sodium permanganate or potassium permanganate is more preferred. Note that these permanganates may be used alone or in combination of two or more.
[0014] In addition, the content of permanganate ions in the polishing slurry of the present invention is preferably 0.5% by mass or more based on the total amount of the polishing slurry of the present invention from the viewpoint of sufficiently increasing the polishing rate.In addition, the content of permanganate ions in the polishing slurry of the present invention is preferably 3.2% by mass or less based on the total amount of the polishing slurry of the present invention from the viewpoint of preventing crystal precipitation due to an increase in the amount of addition, from the viewpoint of ensuring the safety of handling the polishing slurry, and from the viewpoint that the polishing rate tends to saturate even if the amount of addition is increased.That is, the content of permanganate ions is preferably 0.5% by mass or more and 3.2% by mass or less based on the total amount of the polishing slurry of the present invention, and more preferably 1.0% by mass or more and 2.1% by mass or less based on the total amount of the polishing slurry of the present invention.The content of permanganate ions is measured by ion chromatography or absorptiometry.
[0015] Furthermore, the abrasive slurry of the present invention contains phosphoric acid in addition to the manganese oxide abrasive grains and permanganate ions described above. The phosphoric acid can be used in combination with the manganese oxide abrasive grains and permanganate ions to improve the dispersibility of the abrasive slurry of the present invention.
[0016] The phosphoric acid contained in the abrasive slurry of the present invention is preferably, for example, an inorganic phosphorus compound. Specifically, the phosphoric acid compound may be sodium phosphate (trisodium phosphate (anhydrous) (Na3PO4), CAS number: 7601-54-9; trisodium phosphate·12-hydrate (Na3PO4·12H2O), CAS number: 10101-89-0; sodium phosphate monobasic (NaH2PO4), CAS number: 7558-80-7; sodium phosphate dibasic (Na2HPO4), CAS number: 7558-79-4), potassium phosphate (phosphorus Potassium phosphate, tripotassium phosphate (anhydrous) (K3PO4), CAS number: 7778-53-2; potassium phosphate, tripotassium phosphate, monohydrate (K3PO4·H2O), CAS number: 27176-10-9; potassium phosphate, dibasic, trihydrate (K2HPO4·H2O), CAS number: 16788-57-1; potassium phosphate, monobasic (KH2PO4), CAS number: 7778-77-0; potassium phosphate, dibasic (K2HPO4), CAS number: 7758-11-4).
[0017] As a metaphosphate compound, sodium metaphosphate (NaPO3) n , CAS number: 35270-09-8) and potassium metaphosphate (KPO3) n , CAS number: 7790-53-6.
[0018] The hexametaphosphate compound is sodium hexametaphosphate (NaHPO 18 ), CAS number: 10124-56-8.
[0019] Pyrophosphate compounds include sodium pyrophosphate (Sodium pyrophosphate, anhydrous (Na4P2O7), CAS number: 7722-88-5; Sodium pyrophosphate decahydrate (Na4P2O7 10H2O), CAS number: 13472-36-1; Sodium acid pyrophosphate (Na2H2P2O7), CAS number: 7758-16-9) and potassium pyrophosphate (K4P2O7), CAS number: 7320-34-5.
[0020] As a polyphosphate compound, sodium polyphosphate (Na3P3O 10 X2), CAS number: 68915-31-1; Potassium polyphosphate (K3P3O 10 X2), CAS number: 68956-75-2.
[0021] As a tripolyphosphate compound, sodium tripolyphosphate (Na5P3O 10 ), CAS number: 7758-29-4, potassium tripolyphosphate (K5P3O 10 ), CAS number: 13845-36-8.
[0022] Further, salts and hydrates thereof may be mentioned. In the case of these salts, alkali metal salts and alkaline earth metal salts are preferred, and sodium salts and potassium salts are more preferred. In particular, in the abrasive slurry of the present invention, from the viewpoint of effective high dispersibility in a small amount and the viewpoint of sufficiently increasing the polishing rate, metaphosphate compounds, hexametaphosphate compounds, pyrophosphate compounds (sodium pyrophosphate and potassium pyrophosphate), polyphosphate compounds (sodium polyphosphate and potassium polyphosphate) and tripolyphosphate compounds are more preferred. These phosphoric acids may be used alone or in combination of two or more.
[0023] Furthermore, among the inorganic phosphorus compounds described above, pyrophosphate compounds are preferred from the viewpoints of high dispersibility and sufficient increase in polishing rate. Among the pyrophosphate compounds, alkali metal salts of pyrophosphate and alkaline earth metal salts of pyrophosphate are more preferred, and sodium pyrophosphate and potassium pyrophosphate are particularly preferred.
[0024] In addition, the content of phosphoric acid in the abrasive slurry of the present invention is preferably 0.001% by mass or more based on the total amount of the abrasive slurry of the present invention from the viewpoint of dispersibility.In addition, the content of phosphoric acid in the abrasive slurry of the present invention is preferably 0.1% by mass or less based on the total amount of the abrasive slurry of the present invention, because the polishing rate tends to saturate even if the amount of phosphoric acid is increased.That is, the content of phosphoric acid is preferably 0.001% by mass or more and 0.1% by mass or less based on the total amount of the abrasive slurry of the present invention, and more preferably 0.002% by mass or more based on the viewpoint of improving dispersibility, and more preferably 0.05% by mass or less based on the viewpoint of sufficiently increasing the polishing rate.In addition, the content of phosphoric acid in this specification is the total amount of phosphoric acid classified as phosphoric acid, unless otherwise specified.
[0025] Furthermore, the content of phosphoric acids in the abrasive slurry of the present invention, expressed as a mass ratio relative to the content of manganese oxide abrasive grains in the abrasive slurry of the present invention, is preferably 0.05% or more and 5.0% or less, more preferably 0.07% or more and 3.0% or less, and even more preferably 0.1% or more and 2.0% or less.
[0026] The abrasive slurry of the present invention contains, in addition to the manganese oxide abrasive grains, permanganate ions, and phosphoric acids described above, a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formalin condensates, polyvinyl alcohols, polyethylene glycols, polyvinylpyrrolidone, and copolymers thereof. By containing the polymer additive described above, the pot life of the abrasive slurry of the present invention can be extended.
[0027] Furthermore, the water-soluble organic polymer preferably has a number average molecular weight (Mn) of 1000 to 10000, a weight average molecular weight (Mw) of 1000 to 1000000, a z-average molecular weight (Mz) of 5000 to 1000000, a dispersity (Mw / Mn) of 0.1 to 150, and a ratio of Mz to Mw (Mz / Mw) of 0.1 to 20. Here, the number average molecular weight (Mn) is more preferably 2000 to 8000. Typically, the number average molecular weight (Mn) may be 3000 to 6000. The weight average molecular weight (Mw) is more preferably 3500 to 100000, and even more preferably 4000 to 50000. Typically, the weight average molecular weight (Mw) may be 5000 or more and 20000 or less. More preferably, the z-average molecular weight (Mz) is 6000 or more and 100000 or less. Typically, the z-average molecular weight (Mz) may be 6500 or more and 75000 or less, or 7000 or more and 50000 or less. More preferably, the dispersity (Mw / Mn) is 0.5 or more and 75 or less, and even more preferably, 0.8 or more and 10 or less. Typically, the dispersity (Mw / Mn) may be 0.9 or more and 5 or less. More preferably, the ratio of Mz to Mw (Mz / Mw) is 0.5 or more and 15 or less, and even more preferably, 0.8 or more and 10 or less. Typically, the ratio of Mz to Mw (Mz / Mw) may be 0.9 or more and 5 or less. On the other hand, when CMC (carboxymethyl cellulose) is contained as a polymer additive, the pot life of the abrasive slurry is short as described below.
[0028] Here, the number average molecular weight (Mn), weight average molecular weight (Mw), and z average molecular weight (Mz) calculated as polyethylene glycol (PEG) measured by GPC can be measured and analyzed under the following conditions. From the obtained number average molecular weight (Mn), weight average molecular weight (Mw), and z average molecular weight (Mz), the dispersity (Mw / Mn) and the ratio of Mz to Mw (Mz / Mw) are calculated. =Molecular weight measurement conditions= Measurement equipment: HPLC Prominence series (Shimadzu Corporation) Equipment configuration: CBM20A, DGU-20A3R, LC-20AD, SIL-20ACHT, CTO-20AC, RID-10A Column: Shodex OHpak SB-803 HQ (Resonac Co., Ltd.) Temperature: 40℃ Flow rate: 1.0ml / min Detector: Differential refractive index detector Eluent: 0.1M sodium chloride aqueous solution =Analysis software= Software: LabSolutions / LCsolution GPC (Shimadzu Corporation) Version: 1.25 SP2
[0029] Furthermore, when the aqueous solution in which the water-soluble organic polymer is dissolved in water has a high viscosity, it is difficult to measure each molecular weight by the GPC. In that case, it is preferable that the viscosity of the aqueous solution containing 1% by mass of the water-soluble organic polymer at a liquid temperature of 25°C is 10000 mPa·s or more and 30000 mPa·s or less. Typically, the viscosity may be 11000 mPa·s or more and 27000 mPa·s or less, 12000 mPa·s or more and 24000 mPa·s or less, or 13000 mPa·s or more and 21000 mPa·s or less. The viscosity of the water-soluble organic polymer is measured using a digital rotational viscometer DV3T (manufactured by Eiko Seiki Co., Ltd.) and is a value measured under the condition of a rotation speed of 0.01 rpm.
[0030] In addition, in the abrasive slurry of the present invention, the polymer additive is more preferably one or more water-soluble organic polymers selected from polycarboxylic acids, polycarboxylates, and copolymers thereof, further preferably one or more water-soluble organic polymers selected from polyacrylic acid, polymaleic acid, polyacrylates, polymaleates, and copolymers thereof, particularly preferably one or more water-soluble organic polymers selected from polyacrylic acid, polymaleic acid, polyacrylates, polymaleates, and copolymers thereof, particularly preferably one or more polyacrylates, and even more particularly preferably one or more polyammonium acrylates.
[0031] In addition, the content of the polymer additive in the abrasive slurry of the present invention is preferably 0.006% by mass or more based on the total amount of the abrasive slurry of the present invention from the viewpoint of dispersibility.In addition, the content of the polymer additive in the abrasive slurry of the present invention is preferably 0.05% by mass or less based on the total amount of the abrasive slurry of the present invention from the viewpoint of sufficiently increasing the polishing rate.That is, the content of the polymer additive is preferably 0.006% by mass or more and 0.05% by mass or less based on the total amount of the abrasive slurry of the present invention, and more preferably 0.01% by mass or more and 0.03% by mass or less.In addition, in this specification, the content of the polymer additive is the total amount of those classified as the above-mentioned polymer additives, unless otherwise specified.
[0032] Furthermore, the content of the polymer additive in the abrasive slurry of the present invention, expressed as a mass ratio relative to the manganese oxide abrasive grain content in the abrasive slurry of the present invention, is preferably 0.3% or more and 2.5% or less, more preferably 0.4% or more and 2.0% or less, and even more preferably 0.5% or more and 1.0% or less.
[0033] The abrasive slurry of the present invention is characterized in that the content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, the content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, the content of the phosphoric acids is 0.001% by mass or more and 0.1% by mass or less, and the content of the polymer additive is 0.006% by mass or more and 0.05% by mass or less. As described above, the abrasive slurry of the present invention is preferable in that the content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, the content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, the content of the phosphoric acids is 0.001% by mass or more and 0.1% by mass or less, and the content of the polymer additive is 0.006% by mass or more and 0.05% by mass or less, in that the slurry has excellent dispersibility, a high polishing rate, and a long pot life.
[0034] Here, the abrasive slurry of the present invention contains a dispersion medium for dissolving or dispersing the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acids, and polymer additives. The dispersion medium is preferably water, a water-soluble organic solvent such as alcohol or ketone, or a mixture thereof, in order to sufficiently increase the polishing rate, and more preferably water. The content of the dispersion medium is preferably 60% by mass or more and 99.9% by mass or less, and more preferably 80% by mass or more and 90% by mass or less, based on the total amount of the abrasive slurry.
[0035] Furthermore, the abrasive slurry of the present invention may contain any additive other than the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acids, polymer additives, and dispersion medium. Here, the optional additives include dispersants, pH adjusters, viscosity adjusters, chelating agents, and rust inhibitors. The content of the optional additives is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on the total amount of the abrasive slurry of the present invention.
[0036] The abrasive slurry of the present invention can be in a form in which the above-mentioned manganese oxide abrasive grains, permanganate ions, phosphoric acids, polymer additives, dispersion medium, and optional additives are appropriately mixed, and may be, for example, a kit in which these components are divided into two or more agents. The composition of the kit may be in any form that allows the abrasive slurry to fully exhibit its polishing ability when prepared.
[0037] A polishing method for polishing an object to be polished using the above-mentioned abrasive slurry of the present invention will be described below.
[0038] The polishing method includes supplying the abrasive slurry of the present invention to a polishing pad, contacting the polished surface of the workpiece with the polishing pad, and polishing by the relative movement between the two. Here, the method may be a method of pouring the abrasive slurry of the present invention, or a method of circulating the abrasive slurry of the present invention, in which the abrasive slurry of the present invention that has been supplied to the polishing pad and used for polishing is recovered, and the recovered abrasive slurry of the present invention is supplied to the polishing pad again by repeatedly performing the operation. Since the abrasive slurry of the present invention can be circulated and repeatedly used to polish the workpiece, the amount of use can be reduced. Here, the polishing pad can be, for example, a pad made of a nonwoven fabric that has been used conventionally, a pad made by impregnating it with a resin such as polyurethane or epoxy, or a suede material. The polishing pressure is 0.5×10 4 Pa or more 1.0×10 5 Pa or less, especially 1.0×10 4 Pa or more 5.0×10 4 It is preferable that the pressure is not more than Pa in terms of the polishing force and ease of handling of the polishing jig, etc. The supply rate of the abrasive slurry is preferably 10 mL / min to 500 mL / min, and more preferably 50 mL / min to 250 mL / min.
[0039] The object to be polished by the abrasive slurry of the present invention is a high-hardness material having a Mohs hardness of 8 or more. Here, the Mohs hardness is a numerical value of hardness based on the scratching of a standard material, and can be measured by a conventional method using a Mohs hardness meter. Standard materials are designated from 1 to 10 in order of Mohs hardness from softest to softest, and specific standard materials are talc with Mohs hardness 1, gypsum with 2, calcite with 3, fluorite with 4, apatite with 5, orthoclase with 6, quartz with 7, topaz with 8, corundum with 9, and diamond with 10. Examples of high-hardness materials having a Mohs hardness of 8 or more on the Mohs hardness scale include silicon carbide (Mohs hardness about 9), gallium nitride (Mohs hardness about 9), diamond, etc.
[0040] The abrasive slurry of the present invention can be used in a finishing CMP (Chemical Mechanical Polishing) process after lapping of a substrate made of a high hardness material. In particular, the abrasive slurry of the present invention can be used to polish a substrate made of silicon carbide (SiC), i.e., a SiC substrate, and can sufficiently increase the polishing rate and effectively prevent warping and cracking caused by the Twyman effect. A single crystal silicon carbide substrate is usually used as the SiC substrate, and the crystal system thereof is usually hexagonal or rhombohedral, and the hexagonal crystal is preferable from the viewpoint of exerting the effect of the abrasive slurry that can prevent warping and cracking caused by the Twyman effect. The polymorphism of the hexagonal crystal is 2H, 4H, 6H, 8H, and 10H. The polymorphism of the rhombohedral crystal is 15R.
[0041] Next, a method for producing the above-mentioned abrasive slurry of the present invention will be described below.
[0042] First, pure water, manganese dioxide (abrasive grains, MnO2), phosphoric acids (e.g., sodium salt of pyrophosphoric acid), polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formalin condensates, polyvinyl alcohol, polyethylene glucose, polyvinylpyrrolidone, and copolymers thereof, and a polymer additive containing one or more water-soluble organic polymers selected from the group consisting of beads (zirconia, φ0.4 mm) are placed in a container, and the container is set on a paint shaker (60 Hz) and rotated at high speed to mix and grind the manganese dioxide (abrasive grains, MnO2).
[0043] The mixture containing the mixed and ground manganese dioxide (abrasive grains, MnO2) in the container is separated from the beads using a centrifuge (Hitachi Koki himac CT 6E) or the like, and the supernatant liquid is collected.
[0044] The solids concentration in the collected supernatant, ie, the concentration of manganese oxide abrasive grains, is measured using a heating type moisture meter, and pure water is added to the supernatant to reach a predetermined concentration, thereby obtaining an intermediate abrasive slurry.
[0045] The abrasive slurry of the present invention is obtained by mixing the abrasive slurry intermediate with potassium permanganate (KMnO4).
[0046] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention
[0047] The abrasive slurry of the present invention has excellent dispersibility, can sufficiently increase the removal rate, and has a long pot life. [Brief description of the drawings]
[0048] [Figure 1] 1 is a table showing the physical property values and measurement results of abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 5. BEST MODE FOR CARRYING OUT THEINVENTION
[0049] The abrasive slurry according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.
[0050] Example 1 A container was charged with pure water, manganese dioxide (MnO2) as an abrasive, sodium pyrophosphate as a phosphate (specifically, sodium pyrophosphate decahydrate (Na4P2O7·10H2O), CAS number: 13472-36-1), ammonium polyacrylate as a polymer additive (number average molecular weight (Mn): 5500, weight average molecular weight (Mw): 7500, z-average molecular weight (Mz): 9200, degree of dispersion (Mw / Mn): 1.4, ratio of Mz to Mw (Mz / Mw): 1.2), and beads (zirconia, φ0.4 mm). The container was then set on a paint shaker (60 Hz) and rotated at high speed to mix and grind the manganese dioxide. The contents of these components were adjusted so that the manganese dioxide content was 30 mass%, the sodium pyrophosphate content was 0.03 mass%, and the ammonium polyacrylate content was 0.01 mass%, relative to the total amount of the abrasive slurry of Example 1.
[0051] The mixture containing the mixed and ground manganese dioxide in the container was separated from the beads using a centrifuge (Hitachi Koki Himac CT 6E) or the like, and the supernatant was collected. Note that the supernatant obtained in this process will be the measurement sample before the addition of potassium permanganate in the dispersibility test described below.
[0052] The solids concentration in the collected supernatant, ie, the manganese oxide abrasive grain concentration, was measured using a heating moisture meter, and pure water was added to adjust the concentration to a predetermined level, thereby obtaining an intermediate abrasive slurry.
[0053] Then, the abrasive slurry intermediate and an aqueous solution of potassium permanganate (KMnO4) with a KMnO4 mass% concentration of 3.2 mass% were mixed to obtain an abrasive slurry according to Example 1. The content of permanganate ions was adjusted to be 1.2 mass% with respect to the total amount of the abrasive slurry according to Example 1. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive content according to Example 1 was 0.10%. The mass ratio of the total content of polymer additives to the manganese oxide abrasive content according to Example 1 was 0.50%. The abrasive slurry according to Example 1 obtained in this step is the measurement sample after the addition of potassium permanganate in the dispersibility test described later. The composition of the abrasive slurry shown in FIG. 1 is the composition in the final product.
[0054] Example 2 In Example 2, the same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry according to Example 2, except that the manganese dioxide content was adjusted to 0.5 mass% relative to the total amount of the abrasive slurry according to Example 2. The mass ratio of the total content of phosphoric acids relative to the manganese oxide abrasive content according to Example 2 was 0.40%. The mass ratio of the total content of polymer additives relative to the manganese oxide abrasive content according to Example 2 was 2.00%.
[0055] Example 3 In Example 3, the abrasive slurry intermediate was mixed with an aqueous potassium permanganate (KMnO4) solution with a KMnO4 mass% concentration of 5.6 mass%, and the abrasive slurry of Example 3 was prepared so that the content of permanganate ions was 3.2 mass% with respect to the total amount of the abrasive slurry of Example 3. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content of Example 3 was 0.10%. The mass ratio of the total content of polymer additives to the manganese oxide abrasive grain content of Example 3 was 0.50%.
[0056] Example 4 In Example 4, the same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry according to Example 4, except that the content of sodium pyrophosphate was adjusted to 0.001 mass% relative to the total amount of the abrasive slurry according to Example 4. The mass ratio of the total content of phosphoric acids relative to the content of manganese oxide abrasive grains according to Example 4 was 0.05%. The mass ratio of the total content of polymer additives relative to the content of manganese oxide abrasive grains according to Example 4 was 0.50%.
[0057] Example 5 In Example 5, the same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry according to Example 5, except that the content of sodium pyrophosphate was adjusted to 0.1 mass% relative to the total amount of the abrasive slurry according to Example 5. The mass ratio of the total content of phosphoric acids relative to the content of manganese oxide abrasive grains according to Example 5 was 5.00%. Also, the mass ratio of the total content of polymer additives relative to the content of manganese oxide abrasive grains according to Example 5 was 0.50%.
[0058] Example 6 In Example 6, the content of sodium pyrophosphate was 0.0018 mass% relative to the total amount of the abrasive slurry according to Example 6, and other phosphoric acids (specifically, tripotassium phosphate (anhydrous) (K3PO4), CAS number: 7778-53-2, and sodium metaphosphate (NaPO3) n , CAS number: 35270-09-8, potassium pyrophosphate (K4P2O7), CAS number: 7320-34-5, sodium polyphosphate (Na3P3O 10 X2), CAS number: 68915-31-1, and sodium tripolyphosphate (Na5P3O 10 A similar manufacturing method to that of Example 1 was carried out to obtain an abrasive slurry according to Example 6, except that the content of the sample (a mixture of equal amounts of CAS number: 7758-29-4 and CAS number: 7758-29-4) was adjusted to 0.0002 mass%. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive content according to Example 6 was 0.10%. The mass ratio of the total content of polymer additives to the manganese oxide abrasive content according to Example 6 was 0.50%.
[0059] Example 7 In Example 7, the content of the polyacrylic acid ammonium salt was 0.009 mass% and the content of polyvinylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: polyvinylpyrrolidone K25) (number average molecular weight (Mn): 4100, weight average molecular weight (Mw): 14000, z average molecular weight (Mz): 46000, degree of dispersion (Mw / Mn): 3.4, ratio of Mz to Mw (Mz / Mw): 3.3) was 0.001 mass% relative to the total amount of the abrasive slurry according to Example 7. The same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry according to Example 7. The mass ratio of the total content of the phosphoric acid to the manganese oxide abrasive grain content according to Example 7 was 0.10%. The mass ratio of the total content of the polymer additive to the manganese oxide abrasive grain content according to Example 7 was 0.50%.
[0060] Example 8 In Example 8, the same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry according to Example 8, except that the content of ammonium polyacrylate was adjusted to 0.006 mass% relative to the total amount of the abrasive slurry according to Example 8. The mass ratio of the total content of phosphoric acids relative to the manganese oxide abrasive content according to Example 8 was 0.10%. The mass ratio of the total content of polymer additives relative to the manganese oxide abrasive content according to Example 8 was 0.30%.
[0061] Example 9 In Example 9, the same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry according to Example 9, except that the content of ammonium polyacrylate was adjusted to 0.05 mass% relative to the total amount of the abrasive slurry according to Example 9. The mass ratio of the total content of phosphoric acids relative to the manganese oxide abrasive content according to Example 9 was 0.10%. The mass ratio of the total content of polymer additives relative to the manganese oxide abrasive content according to Example 9 was 2.50%.
[0062] Comparative Example 1 In Comparative Example 1, the same production method as in Example 1 was carried out, except that the phosphoric acid and the polymer additive were not added, to obtain an abrasive slurry according to Comparative Example 1.
[0063] Comparative Example 2 In Comparative Example 2, instead of the ammonium polyacrylate used in Example 1, CMC (carboxymethylcellulose) (number average molecular weight (Mn): 12400, weight average molecular weight (Mw): 2400000, z average molecular weight (Mz): 65000000, degree of dispersion (Mw / Mn): 193.5, ratio of Mz to Mw (Mz / Mw): 27.1) was used to prepare 0.25 mass% of the total amount of the abrasive slurry according to Comparative Example 2, by carrying out the same manufacturing method as in Example 1, to obtain an abrasive slurry according to Comparative Example 2. The mass ratio of the total content of phosphoric acids to the manganese oxide abrasive grain content according to Comparative Example 2 was 0.10%. The mass ratio of the total content of polymer additives to the manganese oxide abrasive grain content according to Comparative Example 2 was 12.5%.
[0064] Comparative Example 3 In Comparative Example 3, instead of manganese dioxide (MnO2) used in Example 1, silicon dioxide (SiO2) was used in an amount of 2 mass% relative to the total amount of the abrasive slurry in Comparative Example 3, and potassium permanganate (KMnO4) was not added to the abrasive slurry intermediate, so that the same manufacturing method as in Example 1 was carried out to obtain the abrasive slurry in Comparative Example 3. The mass ratio of the total content of phosphoric acids to the content of silicon oxide abrasive grains in Comparative Example 3 was 0.10%. The mass ratio of the total content of polymer additives to the content of silicon oxide abrasive grains in Comparative Example 3 was 0.50%.
[0065] Comparative Example 4 In Comparative Example 4, the same manufacturing method as in Example 1 was carried out to obtain an abrasive slurry according to Comparative Example 4, except that the content of sodium pyrophosphate was adjusted to 0.5 mass% relative to the total amount of the abrasive slurry according to Comparative Example 4. The mass ratio of the total content of phosphoric acids to the content of manganese oxide abrasive grains according to Comparative Example 4 was 25.0%. The mass ratio of the total content of polymer additives to the content of manganese oxide abrasive grains according to Comparative Example 4 was 0.50%.
[0066] The following physical properties were measured for the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4. The measured physical properties and the methods for measuring the physical properties are shown below, and the measurement results are shown in FIG.
[0067] <Particle size evaluation> The mixtures containing the abrasive grains mixed and ground in a paint shaker in the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4 were diluted with water to a concentration of about 0.01% to prepare measurement samples. Then, the particle size at a volumetric cumulative fraction of 50% (D50) was measured using a laser diffraction / scattering particle size distribution measuring device (MT3300EXII, manufactured by Microtrackbell Corporation).
[0068] <Dispersibility evaluation> The dispersibility of the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 2 and 4 was evaluated before and after the addition of potassium permanganate, which is a source of permanganate ions.
[0069] First, the dispersibility before the addition of potassium permanganate was evaluated as follows. The mixture containing the abrasive grains mixed and ground by a paint shaker in the abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 2 and 4 was diluted with water so that the concentration of the mixture was about 0.01 mass %, to prepare a measurement sample. Then, the particle size (D50) at a volume-based cumulative fraction of 50% was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrackbell Co., Ltd.: MT3300EXII), and if D50 was 0.6 μm or less, it was evaluated as "◯ (Good)", and if D50 was more than 0.6 μm, it was evaluated as "× (Bad)".
[0070] Next, the dispersibility after the addition of potassium permanganate was evaluated as follows. Measurement samples were prepared by diluting the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 2 and 4 with water so that the concentration was about 0.01% by mass. Then, the particle size (D50) at a volume-based cumulative fraction of 50% was measured using a laser diffraction / scattering particle size distribution measuring device (MT3300EXII manufactured by Microtrackbell Co., Ltd.), and if D50 was 0.6 μm or less, it was evaluated as "Good", and if D50 was more than 0.6 μm, it was evaluated as "Bad". Note that the abrasive slurry of Comparative Example 3 did not have potassium permanganate (KMnO4) added to its abrasive slurry intermediate, so the above-mentioned dispersibility evaluation was not performed.
[0071] Adhesion Evaluation The adhesion of the abrasive slurries according to Examples 1 to 9 and Comparative Examples 1 to 4 was judged by a tester by visually observing the adhesion state of each abrasive slurry to the container (wide-mouthed bottle made by AS ONE, Eye Boy 250 ml) containing the sample used in the above-mentioned evaluation of dispersibility after the addition of potassium permanganate, when the container was inverted, as follows. When the container containing the sample was inverted, if the sample did not adhere to the container, it was evaluated as "〇〇 (Very Good)", if the sample adhered only to the bottom of the container, it was evaluated as "〇 (Good)", and if the sample adhered to the bottom and side or side of the container, it was evaluated as "× (Bad)". Note that the abrasive slurry according to Comparative Example 3 was a sample in which potassium permanganate (KMnO4) was not added to the abrasive slurry intermediate.
[0072] <Polishing test> The polishing rates of the abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4 were evaluated by the following procedure. The object to be polished was a CMP-processed 4H-SiC substrate with a diameter of 4 inches and an off angle of 4°. The polishing test was performed on the Si surface of the substrate. The polishing device used was a single-sided polisher BC-15 manufactured by MAT Corporation. The polishing pad attached to the platen was an IC1000 manufactured by Nitta DuPont. The platen rotation speed was set to 60 rpm, and the outer peripheral speed was set to 7,136 cm / min. The carrier rotation speed was set to 60 rpm, and the outer peripheral speed was set to 961 cm / min. Furthermore, the load during polishing was 2.8 psi (approximately 1.96×10 4 The polishing rate was calculated from the difference in the mass of the substrate before and after polishing, after polishing for 1 hour, as shown in Table 1. If the polishing rate was 0.10 μm / h or more, it was evaluated as "Good", and if the polishing rate was less than 0.10 μm / h, it was evaluated as "Bad".
[0073] <Crystallization test> Each sample of Examples 1 to 9 and Comparative Examples 1 to 4 was prepared. Each prepared sample was stored in a refrigerator set at 10° C. for 24 hours. Then, each sample was taken out of the refrigerator, and the solid content concentration in each sample, i.e., the total value of the manganese oxide abrasive grain concentration and the potassium permanganate concentration, was determined using a heating moisture meter. If the solid content concentration after storage maintained 90% or more of the solid content concentration before storage, it was evaluated as "Good (◯)", and if the solid content concentration after storage maintained less than 90% of the solid content concentration before storage, it was evaluated as "Bad (×)".
[0074] <Pot life evaluation> The pot life of Examples 1 to 9 and Comparative Examples 1 to 4 was evaluated as follows. The abrasive slurries of Examples 1 to 9 and Comparative Examples 1 to 4 were left to stand at room temperature (25°C) for three days. The MnO4 - The concentration was measured by the MnO4 concentration in the abrasive slurry before it was left for 3 days. - Compared with the concentration, MnO4 - The retention rate of the concentration was calculated. - Concentration vs. MnO4 after 3 days of standing - If the concentration retention rate is 80% or more, it is evaluated as "Good". - Concentration vs. MnO4 after 3 days of standing - If the retention rate of the concentration was less than 80%, it was evaluated as "Bad". - The concentration was evaluated as follows. First, the abrasive slurry was centrifuged (4,000 rpm x 20 min) to allow the manganese oxide abrasive grains in the abrasive slurry to settle. Next, 1.0 g of the supernatant was taken and diluted with 109 ml of pure water to prepare a diluted solution. Then, the MnO4 - The absorbance of MnO4 was measured and the MnO4 was measured using a calibration curve prepared in advance. - The concentration was calculated.
[0075] As shown in FIG. 1, the abrasive slurries of Examples 1 to 9 had excellent dispersibility, since the particle size at 50% cumulative volume fraction (D50) in the particle size distribution, measured by laser diffraction / scattering method, was 0.6 μm or less both before and after the addition of potassium permanganate, which is a source of permanganate ions.
[0076] In the case of the abrasive slurries of Examples 1 to 6 and 9, when the container containing the sample was inverted and the adhesion state of the abrasive slurries to the container was checked, the sample did not adhere to the container, and the adhesion was very good.In addition, in the case of the abrasive slurries of Examples 7 and 8, when the container containing the sample was inverted and the adhesion state of the abrasive slurries to the container was checked, the sample adhered only to the bottom of the container, and the adhesion was good.
[0077] The abrasive slurries according to Examples 1 to 9 exhibited high polishing rates, since they had polishing rates of 0.10 μm / h or more.
[0078] The abrasive slurries according to Examples 1 to 9 were left at room temperature (25°C) for 3 days, and the MnO4 - Since the concentration was maintained at 80% or more, the pot life was extended.
[0079] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]
[0080] The abrasive slurry of the present invention has excellent dispersibility, high polishing rate, and long pot life, so it is suitable as an abrasive for polishing objects made of high hardness materials.In addition, the abrasive slurry of the present invention has excellent dispersibility, so it is easy to clean the objects to be polished, such as SiC substrates and polishing pads, and it leads to a reduction in environmental load from the viewpoint of reducing the amount of cleaning water used, shortening cleaning time, and reducing wastewater treatment amount.In addition, the abrasive slurry of the present invention has a high polishing rate, so it can shorten the polishing process time.
Claims
1. manganese oxide abrasive grains containing manganese oxide particles; Permanganate ions, a phosphoric acid compound selected from the group consisting of a metaphosphate compound, a hexametaphosphate compound, a pyrophosphate compound, a polyphosphate compound, a tripolyphosphate compound, and salts or hydrates thereof; a polymer additive comprising one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formaldehyde condensates, polyvinyl alcohols, polyethylene glycols, polyvinylpyrrolidones, and copolymers thereof; 13. An abrasive slurry comprising:
2. An abrasive slurry as described in claim 1, characterized in that the content of the phosphoric acids is 0.5 mass % or more and 5.0 mass % or less relative to the manganese oxide abrasive grain content in the abrasive slurry.
3. The content of the manganese oxide abrasive grains is 0.5 mass% or more and 20 mass% or less, The content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, The content of the phosphoric acid is 0.001% by mass or more and 0.1% by mass or less, 2. The abrasive slurry according to claim 1, wherein the content of the polymer additive is 0.006% by mass or more and 0.05% by mass or less.
4. manganese oxide abrasive grains containing manganese oxide particles; Permanganate ions, Phosphoric acids (excluding phosphoric acid and phosphates); a polymer additive comprising one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formaldehyde condensates, polyvinyl alcohols, polyethylene glycols, polyvinylpyrrolidones, and copolymers thereof; An abrasive slurry having 2. An abrasive slurry comprising: a polishing material; and a polishing material that is abrasive-containing slurry having a polishing material and a polishing material that is polished by polishing the polishing material.
5. A manganese oxide abrasive comprising manganese oxide particles; Permanganate ions, Phosphoric acids (excluding phosphoric acid and phosphates); a polymer additive comprising one or more water-soluble organic polymers selected from the group consisting of polycarboxylic acids, polycarboxylates, salts of naphthalenesulfonic acid-formaldehyde condensates, polyvinyl alcohols, polyethylene glycols, polyvinylpyrrolidones, and copolymers thereof; having The content of the manganese oxide abrasive grains is 0.5% by mass or more and 20% by mass or less, The content of the permanganate ions is 0.5% by mass or more and 3.2% by mass or less, The content of the phosphoric acid is 0.001% by mass or more and 0.1% by mass or less, The abrasive slurry has a polymer additive content of 0.006% by mass or more and 0.05% by mass or less.
6. The abrasive slurry according to any one of claims 1 to 5, characterized in that the polymer additive is one or more water-soluble organic polymers selected from polycarboxylic acids, polycarboxylates, and copolymers thereof.
7. The abrasive slurry according to any one of claims 1 to 5, characterized in that the polymer additive is one or more water-soluble organic polymers selected from polyacrylic acid, polyacrylic acid salts, and copolymers thereof.
8. 6. The abrasive slurry according to claim 1, wherein the polymer additive is an ammonium polyacrylate.
9. 6. The abrasive slurry according to claim 1, wherein the phosphoric acid is a pyrophosphate compound.
10. A polishing method comprising polishing an object to be polished with the abrasive slurry according to any one of claims 1 to 5.
Citation Information
Patent Citations
Polishing solution for metal
JP2007258451A
Polishing composition and method for producing polished article
JP2016194004A
Polishing material slurry and polishing method
JP2017071787A
Polishing composition
JP2020045455A
Polishing composition, polishing method of substrate, and manufacturing method of substrate
JP2020055915A